PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM)UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SDN 4 PEKANBARU - Putri, Trieska Rizky Putri Rizky; Marhadi, Hendri Marhadi; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research is a classroom action research (PTK) which aims to improve learning outcomes IPS IVA grade students of SDN 4 Pekanbaru with the implementation of Problem Based Learning Model (PBM). The formulation of the problem is the implementation of Learning Problem Based Learning Model (PBM) can increase student learning outcomes IPS SDN 4 pekanbaru IVA class?this study was conducted on 15 April 2015 s / d May 1, 2015 with the second cycle. The subjects were students of class IVA SDN 4 Pekanbaru, which has 21 students as a source of data. Data collection instruments in this research is the teacher and student activity sheets and written tests, results of this study presents the results obtained from the value of learning daily tests prior to action by an average of 71.14, increasing to 74.76 in the first cycle, increased again to 80.71 in the cycle. The activities of teachers has increased, in the first cycle increased to 65 %% 85 %% in the second cycle. Student activity also increased, in the first cycle of 70% increased to 85% in the second cycle. It can be concluded that the implementation of Problem Based Learning Model (PBM) can improve learning outcomes IPS IVA grade students of SDN 4 Pekanbaru. Keywords: Problem Based Learning, Student Achivement the Result Of Social Studies